Exploring Working Memory Capacity and Efficiency Processes to Understand Working Memory Training Outcomes in Primary School Children - Alexandra S. L. Tan; Regine C. Lau; Peter J. Anderson; Susan Gathercole; Mark A. Bellgrove; Joshua F. Wiley; Megan M. Spencer-Smith (Journal of Cognition, 2024)
Despite the abundance of research evaluating working memory training outcomes in children, few studies have examined the underlying cognitive mechanisms. This study aimed to contribute understanding by exploring whether working memory capacity (maximum span) and/or efficiency (basic and cognitive processing speeds), two proposed cognitive mechanisms, are associated with children’s working memory performance immediately and 6-months post-intervention. We used data from a previous trial in primary school children (7–11 years) who completed working memory training (n = 52) or an active control (n = 36), comprising 10 sessions (each 20-minutes) in class over two weeks. Children completed five working memory measures at baseline, immediately and 6-months post-intervention: two Backwards Span and two Following Instructions measures (same paradigms as training activities), and one n-back measure (different paradigm). Maximum span, basic and cognitive processing speeds, and performance were calculated for each measure. Associations between change in maximum span, processing speeds and change in performance on the working memory measures from baseline to immediately and 6-months post-intervention did not differ between groups (all p < .05). Maximum span, processing speeds and performance on working memory measures did not differ between groups. Findings provide little evidence that the studied capacity or efficiency processes contribute to understanding working memory training outcomes in primary school children. Furthermore, working memory training did not have benefits for children’s working capacity, efficiency or performance up to 6-months post-intervention. It is of interest for future studies to explore cognitive mechanisms, including strategy use, maximum span and information processing, in datasets where training effects are observed.